PERAN WANITA DALAM KEPEMIMPINAN ISLAM (Sejarah Dan Prospek Masa Depan): PERAN WANITA DALAM KEPEMIMPINAN ISLAM (Sejarah Dan Prospek Masa Depan) - Arifin, Miftakul; Rosyidah, Ainur (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
From the beginning of Islam to the present, women's roles in Islamic leadership have undergone significant change. From the historical contributions of Khadijah bint Khuwailid and Aisyah bint Abu Bakar to the challenges and opportunities faced by women in leadership in the modern era, the purpose of this study is to investigate the development of the role of women in leadership in the Islamic world. This study examines how various social, political, and cultural factors have affected women's leadership roles, as well as how current social changes may affect their prospects in the future, using a historical approach and contextual analysis. According to the findings of the study, despite the fact that women have demonstrated significant leadership abilities in a variety of contexts, the extent to which they are able to take on leadership roles is still impacted by a number of obstacles, including how text is interpreted, cultural norms, and structural barriers. However, opportunities for women to take on more active leadership roles are increasing as a result of advancements in education and social change. This study highlights the significance of gaining a deeper comprehension of these dynamics in order to achieve inclusive and sustainable progress. It identifies a number of strategies that can assist women's leadership development in Islamic contexts. Keyword : History, Islamic leadership, the role of women.